Referral to immediate postoperative care in an intensive care unit from the perspective of anesthesiologists, surgeons, and intensive care physicians: a cross-sectional questionnaire - João Manoel Silva, Jr; Henrique Tadashi Katayama; Felipe Manuel Vasconcellos Lopes; Diogo Oliveira Toledo; Cristina Prata Amendola; Fernanda dos Santos Oliveira; Leusi Magda Romano Andraus; Maria José C. Carmona; Suzana Margareth Lobo; Luiz Marcelo Sá Malbouisson (Brazilian Journal of Anesthesiology, 2021)
Introduction and objective: Due to the high cost and insufficient offer, the request for Intensive Care (ICU) beds for postoperative recovery needs adequate criteria. Therefore, we studied the characteristics of patients referred to postoperative care at an ICU from the perspective of anesthesiologists, surgeons, and intensive care physicians. Methods: A questionnaire on referrals to postoperative intensive care was applied to physicians at congresses in Brazil. Anesthesiologists, surgeons, and intensive care physicians who agreed to fill out the questionnaire were included. The questionnaire consisted of hypothetical clinical scenarios and cases for participants to choose which would be the priority for referral to the ICU. Results: 360 physicians participated in the study, with median time of 10 (5–18) years after graduation. Of the interviewees, 36.4% were anesthesiologists, 30.0% surgeons, and 33.6% intensive care physicians. We found that anesthesiologists were more conservative, and surgeons less conservative in ICU referrals. As to patients with risk of bleeding, 75.0% of the surgeons would refer them to the ICU, in contrast with 52.1% of the intensive care physicians, and 43.5% of the anesthesiologists (p < 0.001). As to elderly persons with limited reserve, 62.0% of the surgeons would refer them to the ICU, in contrast with 47.1% of the intensive care physicians, and 22.1% of the anesthesiologists (p < 0.001). As to patients with risk of respiratory complications, 64.5% of the surgeons would recommend the ICU, versus 43.0% of the intensive care physicians, and 32.1% of the anesthesiologists (p < 0.001). Intensive care physicians classified priorities better in indicating ICU, and the main risk indicator was the ASA physical status in all specialties (p < 0.001). There was no agreement among the specialties and surgeries on prioritizing post-operative intensive care. Conclusion: Anesthesiologists, surgeons, and intensive care physicians presented different perspectives on postoperative referral to the ICU.